Implementation of Corporate Social Responsibility (CSR) Study at PT Kereta Api Indonesia (Persero) Regional Division I North Sumatera - Sihombing, Andy Tonggo Michael; Sitorus, Rolib; Sembiring , Higiya Nola (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the regulation and implementation of law on Corporate Social Responsibility at PT KAI DIVRE I SUMUT, and to determine the obstacles to the distribution of assistance and sanctions applicable to the misuse of Corporate Social Responsibility assistance at PT KAI DIVRE I SUMUT. This study uses a normative-empirical legal research type. This study uses two types of data, namely primary data obtained from interviews and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection method in this study is field research and library research. The results of the author's research are that PT KAI DIVRE I SUMUT has carried out its responsibilities and commitments as regulated in existing laws and regulations. There are two obstacles for PT KAI DIVRE I SUMUT in distributing CSR assistance, namely the vast geographical area of ​​North Sumatera and limited funds. Regarding the sanctions that apply if there are CSR aid recipients (community or MSMEs) who misuse CSR, the sanctions given by PT KAI DIVRE I SUMUT are in the form of blacklist sanctions. If there are members of PT KAI DIVRE I SUMUT who misuse the distribution of CSR aid, the sanctions given by PT KAI DIVRE I SUMUT are in the form of Disciplinary Punishment which can be in the form of written warnings, salary deductions and TGR (Demand for Compensation).